Comment - Kaldor, Nicholas (Review of Economic Studies, 1962)
Comment Get access Nicholas Kaldor Nicholas Kaldor Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 29, Issue 3, June 1962, Pages 246–250, https://doi.org/10.2307/2295961 Published: 01 June 1962